Behind the needle perspectives and experiences of select embroiderers and artisans on the commercialization and changing landscape of Lumban's embroidery craft - Baillo, Kathleen Allen Mae P.; Rayala, Maria Monica E. (Quezon City University of the Philippines Diliman, 2025)
This study investigated the experiences and perspectives of embroiderers and artisans in Lumban, Laguna, amidst the evolving embroidery industry shaped by commercialization, changing market demands, and constrained avenues for creative agency. The study used a qualitative descriptive research design with ten (10) purposively selected hand and machine embroiderers aged 19 to 59. It aimed to describe personal and socio-cultural backgrounds of embroiderers and artisans in Lumban; document current embroidery processes and identify changes; determine the embroiderers' and artisans' perceptions of commercialization and its implications; assess the embroiderers' and artisans' current experiences in terms of their visibility, creative agency, and their work's valuation; and describe the current conditions and determine the artisans' recommendations for the improvement of the industry. Data were collected through face-to-face interviews and thematically analyzed. Findings show that the craft remains a vital livelihood passed down through intergenerational transmission and observational learning. While traditional techniques and motifs remain largely intact, subtle changes have emerged, like ethnic-inspired designs and simplification or repetition of older patterns. Though most respondents were unfamiliar with the term “commercialization,” they recognized its impacts: increased demand, greater reliance on machines, and broader market reach. These shifts created economic opportunities but also raised concerns over the declining value of hand embroidery and the rise of machine-made alternatives. They also reported irregular pay, limited creative agency, and lack of recognition; yet, still expressed pride in their craft and its cultural value. This study underscored the need to revalue laborers in both policy and practice to protect their livelihoods and preserve Lumban’s embroidery heritage amid an evolving landscape.
In partial fulfillment for the Degree of Bachelor of Science in Clothing Technology
Thesis
Keywords: Textile crafts; Embroidery— -- Laguna, Philippines; Artisans -- Philippines; Cottage industry; Philippine traditional crafts; Lumban embroidery; Embroiderers; Commercialization